Brain state-dependency of coherent oscillatory activity in the cerebral cortex and basal ganglia of the rat. - Magill, P; Sharott, A; Bolam, J; Brown, P (2004)
The nature of the coupling between neuronal assemblies in the cerebral cortex and basal ganglia (BG) is poorly understood. We tested the hypothesis that coherent population activity is dependent on brain state, frequency range, and/or BG nucleus using data from simultaneous recordings of electrocorticogram (ECoG) and BG local field potentials (LFPs) in anesthetized rats. The coherence between ECoG and LFPs simultaneously recorded from subthalamic nucleus (STN), globus pallidus (GP), and substantia nigra pars reticulata (SNr) was largely confined to slow- ( approximately 1 Hz) and spindle- (7-12 Hz) frequency oscillations during slow-wave activity (SWA). In contrast, during cortical activation, coherence was mostly restricted to high-frequency oscillations (15-60 Hz). The coherence between ECoG and LFPs also depended on BG recording site. Partial coherence analyses showed that, during SWA, STN and SNr shared the same temporal coupling with cortex, thereby forming a single functional axis. Cortex was also tightly, but independently, correlated with GP in a separate functional axis. During activation, STN, GP, and, to a lesser extent, SNr shared the same coherence with cortex as part of one functional axis. In addition, GP formed a second, independently coherent loop with cortex. These data suggest that coherent oscillatory activity is present at the level of LFPs recorded in cortico-basal ganglia circuits, and that synchronized population activity is dynamically organized according to brain state, frequency, and nucleus. These attributes further suggest that synchronized activity should be considered as one of a number of candidate mechanisms underlying the functional organization of these brain circuits.